The Role of Sharia Ta'awun Cooperative in Empowering the Community Economy (Case Study of Sharia Ta'awun Cooperative Klaten Regency) - Rizki, Darlin; Athief, Fauzul Hanif Noor; Agustina, Ricka; Putri, Arum Brawijaya (AL- IKTISAB Journal of Islamic Economic Law, 2022)
••• English ••• This research aims to determine the role of sharia ta'awun cooperatives in community economic empowerment and to find out the opportunities and challenges that exist in sharia ta'awun cooperatives. This type of research is field research, which is carried out using qualitative research. This research method obtains data by means of interviews, documentation, and voice recordings. This research was conducted at the Sharia Ta'awun Cooperative, Klaten Regency. Sources of data used are primary data and secondary data. The data analysis technique used is descriptive qualitative type using a deductive mindset, namely by comparing theory with case studies from the field. The result of this research is the role of sharia ta'awun cooperatives in empowering the community's economy, namely by lending business capital to people in need in order to meet the needs of people's lives and achieve community welfare. While the opportunity in sharia ta'awun cooperative is to provide capital loans and also provide SHU for members who have long been established. In addition, the challenges faced by sharia ta'awun cooperatives are the lack of understanding of the sharia system applied by these cooperatives and the large number of conventional banks that now offer capital loans at low-interest rates. ••• Indonesian ••• Penelitian ini bertujuan untuk mengetahui peran koperasi syariah ta'awun dalam pemberdayaan ekonomi masyarakat serta untuk mengetahui peluang dan tantangan yang ada pada koperasi syariah ta'awun. Jenis penelitian ini adalah penelitian lapangan, yang dilakukan dengan menggunakan penelitian kualitatif. Metode penelitian ini memperoleh data dengan cara wawancara, dokumentasi, dan rekaman suara. Penelitian ini dilakukan di Koperasi Syariah Ta'awun Kabupaten Klaten. Sumber data yang digunakan adalah data primer dan data sekunder. Teknik analisis data yang digunakan adalah tipe deskriptif kualitatif dengan menggunakan pola pikir deduktif, yaitu dengan membandingkan teori dengan studi kasus dari lapangan. Hasil dari penelitian ini adalah peran koperasi syariah ta'awun dalam pemberdayaan ekonomi masyarakat yaitu dengan meminjamkan modal usaha kepada masyarakat yang membutuhkan guna memenuhi kebutuhan hidup masyarakat dan mencapai kesejahteraan masyarakat. Sedangkan peluang dalam koperasi syariah ta'awun adalah memberikan pinjaman modal dan juga memberikan SHU bagi anggota yang telah lama berdiri. Selain itu, tantangan yang dihadapi oleh koperasi syariah ta'awun adalah kurangnya pemahaman tentang sistem syariah yang diterapkan oleh koperasi tersebut dan banyaknya bank konvensional yang sekarang menawarkan pinjaman modal dengan suku bunga rendah.